Seeing Things: literature and the visual - Peter Vernon (dir.) (Presses universitaires François-Rabelais, 2005)
The Papers collected here are representative of the four seminars of the symposium, and, in their various ways, explore many of the concerns of the conference in dealing with literature and various aspects of the visual: painting, cinema, television, theatre, travel writing and photography.